Pola Jaringan Sosial Waria di Kabupaten Empat Lawang - Iklan Sandora, Iklan Sandora; Diana Dewi Sartika, Diana; Andy Alfatih, Andy Alfatih; Isyanawulan, Gita; Putra, Decka Pratama Putra; Ifaty (Electronic Journal of Social and Political Sciences (E-SOSPOL), 2025)
This study's main topic is the discussion of transgender social networks in Empat Lawang Regency's Pendopo District. The phrase "transvestites" describes a phenomenon in which men identify as women by acting or wearing like them, even though they are men. Society considers the transvestite phenomenon to be aberrant. The purpose of this study is to elucidate the social network patterns and existence of transvestites in Pendopo District, Empat Lawang Regency. This study's qualitative technique uses purposeful interviewing to select informants who are knowledgeable about the subjects being covered. The results of the survey show that transvestites are currently rather common in the Pendopo sub-district; they can be seen at residences, weddings, and salons. Transvestites aren't scared to show who they are in public these days. The results of the study also show that women in Pendopo District, Empat Lawang Regency, have established interest networks and emotional networks, two distinct types of social networks. In an attempt to network with other transvestites, gain acceptance in society, and attract customers for their salon business, waria founded the network.